2013
DOI: 10.1002/pts.2049
|View full text |Cite
|
Sign up to set email alerts
|

Rating Accessibility of Packaging: A Medical Packaging Example

Abstract: Few previous work has been undertaken in understanding issues surrounding dexterity and access to packaging. Researchers had access to users who had known dexterity issues and had been advised by their doctor to decant their medication into bottles rather than use unit-dose blister packaging. Hence, it was decided to use a range of techniques to understand this problem. It was further proposed to develop a methodology by which the relative performance of packaging could be assessed with respect to dexterity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Other major factors affecting the opening process include the physical capabilities of users since these capabilities can determine their ability to open packages. Understanding users' capabilities and characteristics will help in designing a user‐friendly package . Packaging characteristics and the choice of opening technique can also affect the opening process.…”
Section: Package Openingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other major factors affecting the opening process include the physical capabilities of users since these capabilities can determine their ability to open packages. Understanding users' capabilities and characteristics will help in designing a user‐friendly package . Packaging characteristics and the choice of opening technique can also affect the opening process.…”
Section: Package Openingmentioning
confidence: 99%
“…These categorizations were further reviewed simultaneously to explore the potential links between them. The review has revealed that the group of seniors was considered as the main group of users tested on medicine packages . This could be explained by the problems they face when using their medications and the importance of providing them with user‐friendly medications packages.…”
Section: Other Possible Categorizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other types of products where the packaging has an active marketing function to influence consumers' decision, medication packaging (in particular, prescription medication) gives the end user limited choice. For many years, the role of medication packaging has been strictly related to safeguarding the contents, with a narrow focus on user needs and packaging design that facilitates human interaction . However, greater attention is being paid to medication packaging today because of its potential to respond to societal challenges and to support patients in their treatment .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have used specially designed force measurement devices for evaluating the opening forces or optical camera techniques to measure grip motions. Rowson et al [14] undertook one of the earliest studies on medical blister packaging using motion-capture, grip and dexterity analysis. The results identified the four common types of grips used, and that participants generally had a preferred grip style.…”
Section: Introductionmentioning
confidence: 99%